2007
DOI: 10.1073/pnas.0707567104
|View full text |Cite
|
Sign up to set email alerts
|

Detection of endogenous biomolecules in Barrett's esophagus by Fourier transform infrared spectroscopy

Abstract: Fourier transform infrared (FTIR) spectroscopy provides a unique molecular fingerprint of tissue from endogenous sources of light absorption; however, specific molecular components of the overall FTIR signature of precancer have not been characterized. In attenuated total reflectance mode, infrared light penetrates only a few microns of the tissue surface, and the influence of water on the spectra can be minimized, allowing for the analyses of the molecular composition of tissues. Here, spectra were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 32 publications
5
68
0
Order By: Relevance
“…Covalently bonded atoms absorb IR radiation corresponding to the specific resonant frequencies of their vibrational motions 24 . It is on this basis that FTIR spectroscopy can be used for characterisation of biological materials such as cultured cells or tissue sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalently bonded atoms absorb IR radiation corresponding to the specific resonant frequencies of their vibrational motions 24 . It is on this basis that FTIR spectroscopy can be used for characterisation of biological materials such as cultured cells or tissue sections.…”
Section: Discussionmentioning
confidence: 99%
“…The main wavenumbers responsible for the separation of spectra from SCs and differentiated cell types are those in the region of 1710-1700 cm -1 (figures 6,7 and 8), around of 1590 cm -1 (figures 7 and 8), the region of 1480 cm -1 ( figure 7 and 8 is associated with sugar ring vibrations 26 and C-O and C-C stretch in DNA 24 .…”
Section: Ptms Instrumentationmentioning
confidence: 99%
“…Recent work by Wang et al has shown that FTIR-ATR measure ments can be used to identify dysplastic and nondysplastic (metaplastic) changes in BE biopsies, with greater diagnostic accuracy than conventional histopathologic interpretation [30]. However in this study, measurements were performed with limited spatial resolution in the horizontal plane, using biopsy samples of approximately 1-mm diameter.…”
Section: "…Fourier Transform Infrared Spectroscopy [Is] Anmentioning
confidence: 99%
“…We should add that in the nucleic acid spectral region we observed also the absorption bands of glycogen around 1032 and 1022 cm −1 (C-O-H bending), 1081 cm −1 (C-C stretching) and 1154 cm −1 (C-O stretching) [30], whose intensities increase starting at day 7 of differentiation ( Fig. 1).…”
Section: Nucleic Acid Changes During Differentiationmentioning
confidence: 99%